From Vision to Metrics: Positioning Australian University-Kuwait for UI GreenMetric Excellece through Digital Transformation - Abidi, Oualid; Abdallah, Farid (Journal of Sustainability Perspectives, 2025)
This study evaluates the sustainability readiness of the Australian University – Kuwait (AU) regarding the UI GreenMetric World University Rankings. Using a qualitative content analysis of AU’s strategic plan and sustainability statements, the research highlights the tangible actions implemented across the six key components: setting and infrastructure, energy and climate change, water conservation, waste management, transportation, and sustainability education and research. Our findings indicate that AU has incorporated tangible sustainability measures in all ranking areas. The most salient initiatives include energy-efficient technologies, smart irrigation, digital transformation to reduce paper use, and partnerships for managing toxic and clinical waste. The university also promotes sustainable commuting through carpooling and bus shuttles. Regarding sustainability education, AU engages the campus community through the organization of seminars, competitions, and international scientific conferences that are gaining wider scope. The study recommends further adoption of advanced digital solutions to enhance the institutional alignment with UI GreenMetric criteria, particularly in water management, thereby building a competitive advantage in the local and regional higher education sectors. This proactive approach is likely to position AU not only for potential ranking inclusion but also as a leader in environmental engagement and digital sustainability in the region.